2013
DOI: 10.1097/mbc.0b013e32835c32ef
|View full text |Cite
|
Sign up to set email alerts
|

Residual thrombosis after a first episode of proximal deep venous thrombosis

Abstract: The aim of this study was to analyse the normalization rate of compression ultrasonography after a first episode of proximal deep venous thrombosis (DVT). Patients underwent compressive ultrasound (C-US) examinations during the 3-6 months following the first proximal DVT episode. Normalization rate of compressive ultrasound (C-US) during the follow-up period was 26.4% [95% confidence interval, 16.3-37.3]. Allelic variation in factor XIII gene (Val34Leu) significantly affected the improvement of popliteal resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…They also suggested that there was a correlation between IL-8 cytokine levels at baseline and the baseline diameter of femoral thrombi. According to their results, resolution of thrombosis at 1 month was associated with severe inflammatory reactions, as measured by plasma markers (higher TNF-a levels) [29]. Spiezia et al [4] found that after an episode of proximal DVT, the thrombus persists over a longer period of time in carriers of thrombophilia than in non-carriers.…”
Section: Discussıonmentioning
confidence: 97%
“…They also suggested that there was a correlation between IL-8 cytokine levels at baseline and the baseline diameter of femoral thrombi. According to their results, resolution of thrombosis at 1 month was associated with severe inflammatory reactions, as measured by plasma markers (higher TNF-a levels) [29]. Spiezia et al [4] found that after an episode of proximal DVT, the thrombus persists over a longer period of time in carriers of thrombophilia than in non-carriers.…”
Section: Discussıonmentioning
confidence: 97%
“…Moderate (odds ratio 2-9) Weak (odds ratio b2) ***Fracture (hip or leg) ***Hip or knee replacement ***Major general surgery ***Major trauma ***Spinal cord injury **Arthroscopic knee surgery **Central venous lines **Chemotherapy **Congestive heart or respiratory failure **Hormone replacement therapy **Malignancy **Oral contraceptive therapy **Paralytic stroke **Pregnancy/, postpartum **Previous venous thromboembolism **Thrombophilia *Bed rest N 3 days *Immobility due to sitting (e.g., prolonged car or air travel) *Increasing age *Laparoscopic surgery (e.g., cholecystectomy) *Obesity *Pregnancy/, antepartum *Varicose veins patients even after a standard anticoagulation therapy, despite the reduction of D-dimer level [24,25]. In another word, it appears that current anticoagulation therapeutic protocols do not target these inflammatory cytokines.…”
Section: Risk Factors For Venous Thromboembolismmentioning
confidence: 99%